Synthesis of imidazo[1,2-a]pyridine-containing peptidomimetics by tandem of Groebke–Blackburn–Bienaymé and Ugi reactions - Kolomiiets, Oleksandr V.; Tsygankov, Alexander V.; Kornet, Maryna N.; Brazhko, Aleksander A.; Musatov, Vladimir I.; Chebanov, Valentyn A. (Beilstein Journal of Organic Chemistry, 2023)
Peptidomimetics with a substituted imidazo[1,2-a]pyridine fragment were synthesized by a tandem of Groebke–Blackburn–Bienaymé and Ugi reactions. The target products contain substituted imidazo[1,2-a]pyridine and peptidomimetic moieties as pharmacophores with four diversity points introduced from readily available starting materials, including scaffold diversity. A small focused compound library of 20 Ugi products was prepared and screened for antibacterial activity.
Keywords: Groebke–Blackburn–Bienaymé reaction; imidazo[1,2-a]pyridine; isocyanide; multicomponent reaction; peptidomimetic; Ugi reaction